Development of porous alumina-hydroxyapatite composites using protein foaming-consolidation method for biomedical applications - Fadli, Ahmad (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
Porous alumina ceramics have been attracting considerable attention for cell loading and bone grafts. Although porous alumina provides relatively high mechanical properties in respect to bioactive porous ceramics, the bioinertness of alumina hamper its application for permanent bone implant. On the other hand, the use of hydroxyapatite (HA) for bone surgery is highly successful due to its biocompatibility, bioactivity and osteoconduction characteristics. The major goal in the present work was to develop a porous alumina-HA composite for biomedical applications. This approach aims to combine the high mechanical strength of the alumina with the biocompatibility of HA ceramics. The alumina-HA porous bodies were fabricated via protein-foaming consolidation method using egg yolk as the pore creating agent. The strategy allows the control of porosity not only by the slurry composition but also by managing the foaming process. Commercial HA, sol-gel derived HA and commercial alumina powders were mixed with yolk and starch as well as darvan 821A at an adjusted ratio. The resulting slip was poured into cylindrical shaped molds and followed by foaming and consolidation via 180°C drying for 1 hour. The obtained green bodies were burned at 600° for 1 hour, followed by sintering at various temperatures (1200-1550°C). The slurry drying at high temperatures resulted in high foaming capacity and bigger pore sizes as well as privileged pore generation. The increasing yolk and dispersant concentrations in slurries transmitted the rheological conditions from pseudoplastic behavior to Newtonian fluid. Porous alumina-HA bodies with shrinkage in the range of 26-77 vol.% and porosity of 46-52% as well as compressive strength of 0.1 – 6.4 MPa were obtained. The compressive strength of porous alumina-HA bodies increased with increasing sintering temperatures. The addition of commercial HA in the body was found to increase the compressive strength, whereas the case is reversed for the addition of sol-gel HA. FESEM analysis of cultured cells showed a good compatibility of the Vero cells to the porous microcarriers, since the cells were obviously attached at the surface of microcarriers at 8 – 120 cultured hours. The cell growth of porous alumina microcarrier was 0.015 h-1 and increased to 0.019 h-1 for 0.3 w/w HA-to-alumina mass ratio and decreased again to 0.017 h-1 for 1.0 w/w ratio. Carbon concentrations on porous alumina bodies without HA addition was 36.03%; it significantly increased 46.14% when 1.0 w/w HA was added.